1990
DOI: 10.1111/j.1151-2916.1990.tb05190.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Core‐Shell Grains on the Internal Stress State and Permittivity Response of Zirconia‐Modified Barium Titanate

Abstract: BaTi03 modified with grain-boundary resident ZrOl ( 5 2 wt%) results in substantial chemical modification of the microstructure when sintered at 1320°C for 2 h. These modified regions were seen as core-shell grains in the microstructure and were accompanied by an increase in the internal stress level. The shells had a variable composition (Ba(TiI-rZrx)03) and a tetragonal structure. An expansion mismatch between the core and the shell placed the core in compression resulting in a decrease in the lattice parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
74
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 13 publications
11
74
2
Order By: Relevance
“…It should be noted that the c lattice parameter decreases monotonously ( Table 2). Armstrong et al figured that [7] the great internal stress caused by the high expansion shell forced a decrease in the c lattice parameter and thus tetragonality decreased. Figure 3(a) shows the temperature dependence of dielectric constant for all the samples.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that the c lattice parameter decreases monotonously ( Table 2). Armstrong et al figured that [7] the great internal stress caused by the high expansion shell forced a decrease in the c lattice parameter and thus tetragonality decreased. Figure 3(a) shows the temperature dependence of dielectric constant for all the samples.…”
Section: Resultsmentioning
confidence: 97%
“…It has been proved that the characteristic of broadened permittivity-temperature represents a diffuse phase transition (DPT) around T c, and this behavior was observed in BaTiO 3 with additive of ZrO 2 [5] . Armstrong and Lu et al [6,7] reported that ZrO 2 -modified BaTiO 3 showed a suppressed ferroelectric transition region by the influence of core-shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…The core-shell structure boundary as indicated by A in Fig. 3(a) is suggested to be coherent [16][17][18]21]. The thickness of the domains varies between grains, but is generally less than 100 nm.…”
Section: Resultsmentioning
confidence: 96%
“…It is widely accepted that the presence of core-shell structures in ceramics is attributed to chemical inhomogeneity [15][16][17][18][19][20]. Armstrong and Buchanan [21] used convergent beam electron diffraction (CBED) in the transmission electron microscope (TEM) to determine that both the core and shell in zirconia-modified barium titanate were tetragonal phases at room temperature. However, cubic shell phases have also been reported by other researchers in barium titanate systems doped with other additives [19].…”
Section: Introductionmentioning
confidence: 99%
“…Its dissipation factor is higher at low temperature than that of other samples. For such a difference in dielectric-temperature behavior among samples, several causes have been proposed, including differences in (a) the concentration of dopants in the shell [19,34], (b) the occupational site of rare-earth elements in the shell [16][17][18]35], (c) charge carrier concentrations and the resultant valence state of Ti [27,28], and (d) the residual strain [24,36]. In this study, the effect of the concentration of dopants can be excluded because all the samples were prepared under the same experimental conditions, except the oxidation temperature, which should not affect the distribution of dopants in the shell.…”
Section: Resultsmentioning
confidence: 99%